Lembaga Getah Malaysia (LGM) / Siti Nur Ain Ramly ... [et al.] - Siti Nur Ain, Ramly; Alyani Izzati, Mohd Zainal; Nur Amira Adilla, Mustaffa Kamal; Nazifa, Mohhidin; Muhammad Zulhusni, Dahlan (2019)
This report is about our case study where is Lembaga Getah Malaysia. We have visited our case study for five times to completed the information in this report. From this report we know the building only using planned and unplanned maintenance strategy for their maintenance. This report has 10 chapters where’s every chapter have different contents. For the chapter 1 is shows about the detail of property. For chapter 2, it shows the organization for maintenance management of the company. For chapter 3, it shows the maintenance policy and planning for the company. Chapter 4 shows the building design and technology design. For chapter 5, it shows the condition assessment of the building. Chapter 6, shows the maintenance strategy of the building. Chapter 7, shows the legal aspect of the building. It is about the building agreements with the tenants and contractor. For chapter 8, is about the financial analysis for 2019 and the forecasting years. For chapter 9, shows about the problems and recommendation of the problems in the building. For the last chapter, chapter 10, it shows the conclusion of our report.